2012
DOI: 10.1002/iub.603
|View full text |Cite
|
Sign up to set email alerts
|

Nanomolar melatonin enhances nNOS expression and controls HaCaT‐cells bioenergetics

Abstract: SummaryA novel role of melatonin was unveiled, using immortalized human keratinocyte cells (HaCaT) as a model system. Within a time window compatible with its circadian rhythm, melatonin at nanomolar concentration raised both the expression level of the neuronal nitric oxide synthase mRNA and the nitric oxide oxidation products, nitrite and nitrate. On the same time scale, a depression of the mitochondrial membrane potential was detected together with a decrease of the oxidative phosphorylation efficiency, com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 48 publications
4
36
0
Order By: Relevance
“…In the present study, the peak of nNOS expression was observed around 10 a.m., that is, it occurred around seven hours after the peak of melatonin reported by the previous study on melatonin rhythm in pigeons conducted in our laboratory [53]. So, these results are consistent with the findings on the temporal expression of nNOS mRNA in in vitro study with human cells [50]. …”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In the present study, the peak of nNOS expression was observed around 10 a.m., that is, it occurred around seven hours after the peak of melatonin reported by the previous study on melatonin rhythm in pigeons conducted in our laboratory [53]. So, these results are consistent with the findings on the temporal expression of nNOS mRNA in in vitro study with human cells [50]. …”
Section: Discussionsupporting
confidence: 93%
“…These findings indicate that the SCN can indirectly modulate Ca 2+ stimulated adenylyl ciclase in the hippocampus during the circadian cycle by controlling the release of melatonin from the pineal gland, which is a major efferent pathway of the biological timing system [47]. The expression and activity of both nNOS and iNOS proteins may be dependent on circadian timing system and according to recent evidence melatonin may be involved in the regulation of these mechanisms [48-50]. A transient but substantial rise of the constitutive nNOS was observed when cultured cells were incubated during 6 hours with 1 nM melatonin volume [50].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Noticeably, in the presence of enough O 2 (5 ÷ 20  μ M) and a suitable electron flux through the respiratory chain sustained by the mitochondrial substrates and reduced cytochrome c , the presence of nanomolar NO does not depress (significantly) cell respiration. Interestingly, from the bioenergetics signaling point of view, under these conditions, the apparent affinity for O 2 ( K M , O2 ) of cytochrome c oxidase (CcOX) rises [55], and the mitochondria become sensitive to the O 2 concentration, thus ready to shift to glycolytic production of ATP [56, 57]. Under persistent hypoxic conditions, when the mitochondrial respiratory chain experiences for longer times a too low (insufficient) O 2 concentration, a different landscape could be depicted.…”
Section: Mitochondrial Toxicity and Molecular Targetsmentioning
confidence: 99%
“…However, these effects are sometimes conditional or tissue-specific. While melatonin is known to antagonize the activation of neuronal NO synthase (nNOS) in the central nervous system, it was shown to up-regulate nNOS expression in HaCaT keratinocytes [130,131]. The quantities of NO formed were sufficient to decrease mitochondrial membrane potential and oxidative phosphorylation and may serve as a signal connecting the circadian system to mitochondrial function [131].…”
Section: Epigenetics Of Inflammation and Oxidative Stress Vs Antimentioning
confidence: 99%